Pengaruh Environmental Concern, Fear Of Missing Out (FOMO), Dan Corporate Governance Terhadap Keputusan Investasi Saham Pada Generasi Z (Studi Kasus Mahasiswa FEB Universitas Islam Malang Angkatan 2021) - Rizky Nanda Firmansyah; Agus Widarko; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The aim of this research is to determine and examine the impact of Environmental Concern, Fear of Missing Out (FOMO), and Corporate Governance on stock investment decisions among Generation Z. This study employs an explanatory research method with a quantitative approach, using a Likert scale as the measurement instrument. Purposive sampling was applied with predetermined criteria, resulting in a total of 87 respondents. Primary data were collected through the distribution of questionnaires using Google Forms. The data analysis methods included validity and reliability tests, normality tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination analysis using SPSS version 25. The results of this study indicate that Environmental Concern, Fear of Missing Out (FOMO), and Corporate Governance simultaneously influence stock investment decisions among Generation Z. Environmental Concern does not have a significant effect on stock investment decisions among Generation Z. Fear of Missing Out (FOMO) has a significant effect on stock investment decisions among Generation Z. Corporate Governance has a significant effect on stock investment decisions among Generation Z. Keywords: Environmental Concern, Fear of Missing Out (FOMO), Corporate Governance, Stock Investment Decision, Generation Z.